Design and implementation of low-cost hardware architecture for authentication encryption algorithm SM4-GCM - Rui CHEN; Chunqiang LI (物联网学报)
The internet of things (IoT) has gained wide adoption across various industries, driving digitalization and intelligence in industry applications.However, the data collected by IoT devices in some industry applications may be closely linked to user privacy and property security.To ensure the security of such data, a cost-effective, multifunctional hardware architecture design based on the Chinese authenticated encryption algorithm SM4-GCM (Galois/Counter Mode) was proposed, which offered a balanced approach to performance, cost, and hardware-level data confidentiality and integrity assurance, and supported three operation modes: SM4-CTR, SM4-ECB, and SM4-GCM.The implementation results on the field programmable gate array (FPGA) development board demonstrate that the design requires only 1 761 look-up tables and 1 825 registers, occupies only 604 slices, and has a throughput rate of 39.78 Mbit/s@100 MHz.These results suggest that the proposed design can effectively meet the requirements of IoT data security applications.